Lloyd's introducation to jurisprudence - "Freeman, Michael" (London, 2014)
Lloyd$1 (Bs Introduction to Jurisprudence is the leading textbook on jurisprudence in the English-speaking world. It enables the reader to develop a good understanding of the theories of the different schools of jurisprudence, and to appreciate the contributions made to legal theory by leading jurists and others, from the Ancient Greeks to the postmodernists.s
Keywords: "Jurisprudence:Freeman,M.D.A.:Law"